Online Language Teaching: A Bibliometric Analysis - Ranasinghe, Lakshani; Iddagoda, Anuradha; Dissanayake, Hiranya (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
For decades, researchers have been researching online education. Numerous scholarly works have concentrated on online teaching and learning theories, as well as quality online learning and online course design assessment criteria. This is a bibliometric analysis. Online Language Teaching is the keyword is considered for the analysis. Publications taken from the Scopus database from 2006 to 2022. Only the English language articles are selected. The final database comprises 74 articles in this area of research. The objectives of the study are: (1) To examine the trend of publications related to “Online Language Teaching”; (2) To examine the highly cited authors related to “Online Language Teaching”; (3) To examine the highly cited sources related to “Online Language Teaching”; (4) To examine the highly cited countries related to “Online Language Teaching”; (5) To examine the frequently used keywords related to “Online Language Teaching”; (6) To recommend future research opportunities related to “Online Language Teaching”.